A critical appraisal of tools for delivery room assessment of the newborn infant - Niemuth, M; Küster, H; Simma, B; European Society for Paediatric Research (ESPR) Neonatal Resuscitation Section Writing Group; Solevåg, AL (Springer Nature, 2021)
Assessment of an infant’s condition in the delivery room represents a prerequisite to adequately initiate medical support. In her seminal paper, Virginia Apgar described five parameters to be used for such an assessment. However, since that time maternal and neonatal care has changed; interventions were improved and infants are even more premature. Nevertheless, the Apgar score is assigned to infants worldwide but there are concerns about low interobserver reliability, especially in preterm infants. Also, resuscitative interventions may preclude the interpretation of the score, which is of concern when used as an outcome parameter in delivery room intervention studies. Within the context of these changes, we performed a critical appraisal on how to assess postnatal condition of the newborn including the clinical parameters of the Apgar score, as well as selected additional parameters and a proposed new scoring system. The development of a new scoring system that guide clinicians in assessing infants and help to decide how to support postnatal adaptation is discussed.